2019
DOI: 10.1029/2019ja027445
|View full text |Cite
|
Sign up to set email alerts
|

MELISSA: System description and spectral features of pre‐ and post‐midnight F‐region echoes

Abstract: Most of the low-latitude ionospheric radar observations in South America come from the Jicamarca Radio Observatory, located in the western longitude sector (∼ 75 • W). The deployment of the 30 MHz FAPESP-Clemson-INPE (FCI) coherent backscatter radar in the magnetic equatorial site of São Luis, Brazil, in 2001 allowed observations to be made in the eastern sector (∼ 45 • W). However, despite being operational for several years (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), FCI only ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Multiple previous studies have concluded that post-midnight bubbles are the extension of bubbles generated during pre-midnight local time sector (Huang et al, 2014). Other studies, using ground based passive VHF (Yizengaw et al, 2013) and active backscatter (Patra et al, 2009;Rodrigues et al, 2019) radars, even observed post-midnight strong scintillation and field-aligned irregularity structures, respectively, during the nights when no pre-midnight irregularity pattern observed. All this confirms that the DGRI index can be used as a proxy to characterize ionospheric bubbles/irregularities and identify "all clear" zone at all local times.…”
Section: Resultsmentioning
confidence: 94%
“…Multiple previous studies have concluded that post-midnight bubbles are the extension of bubbles generated during pre-midnight local time sector (Huang et al, 2014). Other studies, using ground based passive VHF (Yizengaw et al, 2013) and active backscatter (Patra et al, 2009;Rodrigues et al, 2019) radars, even observed post-midnight strong scintillation and field-aligned irregularity structures, respectively, during the nights when no pre-midnight irregularity pattern observed. All this confirms that the DGRI index can be used as a proxy to characterize ionospheric bubbles/irregularities and identify "all clear" zone at all local times.…”
Section: Resultsmentioning
confidence: 94%